2016
DOI: 10.1097/md.0000000000003913
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of dilated blood vessels in the tumor periphery for assessing the invasion depth of small-sized depressed colorectal cancer

Abstract: The relationship between dilated blood vessels in the tumor periphery and the tumor invasion depth is unclear. Therefore, the present study aimed to clarify the relationship between dilated blood vessels and the invasion depth of small-sized (<30 mm) colorectal cancer (CRC), and its implications on endoscopic treatment.We performed a single-arm observational study of the diagnostic accuracy of the existence of dilated vessels in the tumor periphery of CRC lesions as an indicator of submucosal deep (SM-d, ≥1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In contrast, deep submucosal (dSM) invasive cancer is classified as type 3, which shows avascular or loose vascular areas or disrupted thick vessels and an invisible amorphous surface pattern. 4,5 In addition, other reports have suggested that the microvascular structure differs depending on the histological type of colon tumor. 6,7 Based on these findings, we speculate that tumors with higher microvascular density (MVD) should tend to have higher-grade histology and deeper intramural invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, deep submucosal (dSM) invasive cancer is classified as type 3, which shows avascular or loose vascular areas or disrupted thick vessels and an invisible amorphous surface pattern. 4,5 In addition, other reports have suggested that the microvascular structure differs depending on the histological type of colon tumor. 6,7 Based on these findings, we speculate that tumors with higher microvascular density (MVD) should tend to have higher-grade histology and deeper intramural invasion.…”
Section: Introductionmentioning
confidence: 99%